PSYCHOLOGICAL EFFECTS OF DOMESTIC VIOLENCE ON THE BEHAVIOUR OF ADOLESCENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
the article examines the influence of family factors on the behavior of adolescents, in particular, family violence. The types, manifestations, and causes of domestic violence are analyzed psychologically. Ways to eliminate them have been developed.